Religious institutions in 19th-century Tehran: shariʿa law in a city in transition - Nasrollahi, R (2022)
The Nāṣirī period (5 September 1848 CE to 1 May 1896 CE) was a period of massive social transition embedded in the pretext of the Iranian modernization process. The rapid multidimensional developments of Iranian society turned it into a unique time frame for applying an institutional approach to socio-historical research. By concentrating on the continuity and change of the Shiʿi religious institutions (RIs) in Iranian society, this research investigates how social groups and institutions facilitated changes in RIs. The research chooses a set of RIs which have had a unique status in the Iranian society: waqf, mosque, takyih, madrasa, and imāmzādih.